Forecasting model for the number of long stay Japanese tourist arrivals in Chiang Mai - PRADTHANA MINSAN; KUNANON JOMTOUR; WATHA MINSAN (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: Japan has the oldest average population of any country in the world, and its elderly population is ageing at an alarming rate. As a result, long-stay tourism provides an alternate form of tourism for Japanese retirees. This study aimed to develop a reliable model for predicting the influx of Japanese visitors planning to spend an extended amount of time in Chiang Mai, Thailand.Method: This study used data collected from the Chiang Mai Immigration Office for 43 months, beginning in January 2014 and ending in July 2017. After that, we divided the information into two groups. The forecasting model was developed using Classical decomposition, Seasonal analysis, simple exponential smoothing, Box-Jenkins, and Combining the first data set covering 36 months from January 2014 to December 2016. The RMSE criterion was used to compare the three earlier methods of forecasting accuracy on a second data set spanning January 2017 to July 2017.Findings: Combining forecasts was found to be the most appropriate method of forecasting the expected number of long-term Japanese visitors to Chiang Mai.Implications/Novel Contribution: Chiang Mai, Thailand, is a popular destination for Japanese travellers, but a look through academic journals reveals that nobody has published any research on predicting the number of Japanese visitors staying in the city for an extended period. Therefore, this study substantially advances the existing body of literature.